Taxonomic notes on hexapogon irises (Iridaceae) - Boltenkov, Eugeny V. (Phytotaxa, 2017)
The taxonomic notes in this article are based on the result of an analysis of the protologues, relevant literature, and a study of herbarium specimens of Iris sect. Hexapogon. This section comprises species with bearded claw in both outer and inner segments of perianth. These are relatively poorly known psammophytes occurring mostly in the desert and semi-desert regions of some of the former Soviet Central Asian republics, as well as in Iran, Afghanistan and Pakistan (Baluchistan). It is now generally accepted that I. sect. Hexapogon comprises two species, I. falcifolia and I. longiscapa. The present study has shown that this section contains only I. longiscapa. The name I. falcifolia is for the first time reduced to a synonym of I. longiscapa. A neotype for the name I. longiscapa and lectotypes for the names I. falcifolia and I. filifolia are designated. Notes are provided on the original material for all the three considered names.